Continuous microalgae cultivation in a photobioreactor - Tang, Haiying; Chen, Meng; Simon Ng, K.Y.; Salley, Steven O. (Biotechnology and bioengineering, 2012)
New biomass sources for alternative fuels has become a subject of increasing importance as the nation strives to resolve the economic and strategic impacts of limited fossil fuel resources on our national security, environment, and global climate. Algae are among the most promising non‐food‐crop‐based biomass feedstocks. However, there are currently no commercially viable microalgae‐based production systems for biofuel production that have been developed, as limitations include less‐than optimal oil content, growth rates, and cultivation techniques. While batch studies are critical for determining basic growth phases and characteristics of the algal species, steady‐state studies are necessary to better understand and measure the specific growth parameters. This study evaluated the effects of dilution rate on microalgal biomass productivity, lipid content, and fatty acid profile under steady‐state conditions with continuous illumination and carbon dioxide supplemention for two types of algae. Continuous cultures were conducted for more that 3 months. Our results show that the productivity of Chlorella minutissima varied from 39 to 137 mg/L/day (dry mass) when the dilution rate varied from 0.08 to 0.64 day−1. The biomass productivity of C. minutissima reached a maximum value (137 mg/L/day) at a dilution rate of 0.33 day−1, while the productivity of Dunaliella tertiolecta varied from 46 to 91 mg/L/day at a dilution rate of 0.17 to 0.74 day−1. The biomass productivity of D. tertiolecta reached a maximum value of 91 mg/L/day at a dilution rate of 0.42 day−1. Moreover, the lipid content had no significant change with various dilution rates. Biotechnol. Bioeng. 2012; 109: 2468–2474. © 2012 Wiley Periodicals, Inc. Chlorella minutissima continuous cultivation in a 3L photobioreactor was performed with continuous light of 50 µE/(m2 s) initial light intensity using white LEDs, and 4% CO2, at a temperature of 25°C. The maximum biomass and total FAME productivity were 137 mg/L/day and 6 mg/L/day at an optimal dilution rate of 0.328 day−1.